1982
DOI: 10.1083/jcb.95.3.943
|View full text |Cite
|
Sign up to set email alerts
|

Ca++-calmodulin-dependent phosphorylation of myosin, and its role in brush border contraction in vitro.

Abstract: We have reinvestigated the effects of Ca ++ and ATP on brush borders isolated from intestinal epithelial cells. At 37°C, Ca ++ (1/tM) and ATP cause a dramatic contraction of brush border terminal webs, not a retraction of microvilli as previously reported (M. S. Mooseker, 1976, J. Cell Biol. 71:417-433). Terminal web contraction, which occurs over the course of 1-5 min at 37°C, actively constricts brush borders at the level of their zonula adherens. Contraction requires ATP, is stimulated by Ca ++ (1 /xM), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(89 citation statements)
references
References 74 publications
2
86
1
Order By: Relevance
“…We also observed a reduction in the density of cross-linking filaments associated with the basal ends of the core rootlets. In addition, the circumferential, "contracting" ring (37,35,48,49) of actin filaments associated with the junctional margin of the brush border at the level ofthe zonula adherens was intact in the salt-extracted brush borders, but it appeared somewhat less densely packed than in control preparations (results not shown, but see reference 37) . Numerous crosslinking filaments resembling myosin filaments (Fig.…”
Section: Structurementioning
confidence: 89%
See 1 more Smart Citation
“…We also observed a reduction in the density of cross-linking filaments associated with the basal ends of the core rootlets. In addition, the circumferential, "contracting" ring (37,35,48,49) of actin filaments associated with the junctional margin of the brush border at the level ofthe zonula adherens was intact in the salt-extracted brush borders, but it appeared somewhat less densely packed than in control preparations (results not shown, but see reference 37) . Numerous crosslinking filaments resembling myosin filaments (Fig.…”
Section: Structurementioning
confidence: 89%
“…For example, TW 260/240 may participate in endocytosis of apical membrane, which is mediated, at least in part, by coated vesicles (53). In addition, apical membrane may be replaced by Goggi-derived vesicles (54) that we have speculated are actively transported to the membrane along core rootlets, perhaps by vesicle-associated myosin (35,37). This speculation was based on the observation that in QFDERR preparations of isolated brush borders there are numerous vesicles attached to the core rootlets.…”
Section: Possible Functions For Tw 260/240mentioning
confidence: 99%
“…However, long-term exposure of endothelial monolayers to low Ca2+ finally caused (beginning about 60 min after addition of EDTA) disintegration of the monolayer and a concomitant rise in permeability. TFP and W7, two compounds known to interfere with Ca2+-calmodulin-dependent mechanisms such as stimulation of actin-activated myosinATPase (Sheterline, 1980;Hidaka, Asano & Tanaka, 1981;Keller & Mooseker, 1982;Sobieszek, 1989), inhibited both the Ca2+/A23187-induced rise in permeability (Fig. 8B) and gap formation (Fig.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Previous reports indicated that the Ca 2C /calmodulin-dependent phosphorylation of MLC induced TW contraction associated with BB fanning on isolated brush border sheets interconnected by TJs. 51,52 We speculated that ultrastructural changes of the BB were required to allow entry of intestinal bacteria into cells. By using human C2BBe cell cultures (a clone of Caco-2 cells with long BB), we demonstrated that IFNg stimulation caused internalization of nonpathogenic bacteria by epithelial cells through a cholesterol-rich lipid raft and caveolin-1-dependent endocytotic pathways.…”
Section: Terminal Web Contraction and Brush Border Fanningmentioning
confidence: 99%